Comparative chloroplast genome analyses of Oxytropis DC. species: new insights into genome evolution and phylogenomic implications - Li, Qin-Qin; Niu, Yan; Zhang, Zhi-Ping; Wen, Jun; Liao, Chen-Yang (Frontiers in Plant Science, 2025)
The genus Oxytropis DC. comprises about 310 species distributed in Asia, Europe, and North America. Previous studies based on evidences from morphology or a few molecular markers are helpful for understanding the classification and systematic evolution of Oxytropis. However, a scarcity of chloroplast genomic resources for Oxytropis has hindered the understanding of the genus’s systematic classification and chloroplast genome evolution. Here comparative genomic analyses were conducted on chloroplast genomes of 24 Oxytropis species. Chloroplast genomes of Oxytropis species showed the triad structure due to the loss of one copy of the IR, with the size range from 121854 bp to 125271 bp. The Oxytropis cp genomes encoded a total of 110 genes, including 76 protein-coding genes (PCGs), 30 transfer RNA (tRNA) genes, and four ribosomal RNA (rRNA) genes. It was found that the atpF intron, one clpP intron, one rps12 intron, rpl22 gene, rps16 gene, and infA gene were lost in the Oxytropis cp genomes. Seven regions (5’-rps12-clpP, clpP intron, psbM-petN, rpl23-trnI-CAU, ndhJ-trnF-GAA,trnQ-UUG-accD, trnL-UAA-trnT-UGU) were chosen as potential molecular markers, which will contribute to species identification, population genetics and phylogenetic studies of Oxytropis. The phylogenetic relationships among Oxytropis species provided some implications for the classification of Oxytropis. Congruent with studies based on the morphological evidence, the close relationships between O. neimonggolica and O. diversifolia, as well as O. filiformis and O. coerulea were revealed. The results supported the treatment of O. daqingshanica as a separate species and refuted the inclusion of O. daqingshanica in O. ochrantha as conspecific taxa. In addition, it was suggested that O. chiliophylla should be considered as a separate species rather than its inclusion in O. microphylla. The 16 positively selected genes (rps3, rps4, rps7, rps11, rps12, rpl2, rpl20, rpl32, rpoC2, psbC, rbcL, atpF, clpP, accD, ycf1, ycf2) are related to important biological processes for instance self-replication, photosynthesis and metabolite biosynthesis, which may contribute to the adaptation of Oxytropis to its habitats. This study will lay a solid foundation for further studies on species identification, taxonomy, and systematic evolution of Oxytropis.